The endothelium: gatekeeper to lung ischemia-reperfusion injury - Huy Q. Ta; Maniselvan Kuppusamy; Swapnil K. Sonkusare; Mark E. Roeser; Victor E. Laubach (2024)
Abstract The success of lung transplantation is limited by the high rate of primary graft dysfunction due to ischemia-reperfusion injury (IRI). Lung IRI is characterized by a robust inflammatory response, lung dysfunction, endothelial barrier disruption, oxidative stress, vascular permeability, edema, and neutrophil infiltration. These events are dependent on the health of the endothelium, which is a primary target of IRI that results in pulmonary endothelial barrier dysfunction. Over the past 10 years, research has focused more on the endothelium, which is beginning to unravel the multi-factorial pathogenesis and immunologic mechanisms underlying IRI. Many important proteins, receptors, and signaling pathways that are involved in the pathogenesis of endothelial dysfunction after IR are starting to be identified and targeted as prospective therapies for lung IRI. In this review, we highlight the more significant mediators of IRI-induced endothelial dysfunction discovered over the past decade including the extracellular glycocalyx, endothelial ion channels, purinergic receptors, kinases, and integrins. While there are no definitive clinical therapies currently available to prevent lung IRI, we will discuss potential clinical strategies for targeting the endothelium for the treatment or prevention of IRI. The accruing evidence on the essential role the endothelium plays in lung IRI suggests that promising endothelial-directed treatments may be approaching the clinic soon. The application of therapies targeting the pulmonary endothelium may help to halt this rapid and potentially fatal injury.